2018
DOI: 10.1111/age.12713
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analyses of lesion counts in group‐housed pigs

Abstract: Aggression in group-housed pigs is a welfare concern and can negatively affect production. Skin lesions are reliable indicators of aggression and are moderately heritable, suggesting that selective breeding may reduce aggression. To further understand the genetic control of behavioral traits, such as the aggressive response to regrouping, associated single nucleotide polymorphisms (SNPs) can be identified within the genome, and the region in which these SNPs are located can be related to known genes. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Besides, PL and IMF of this resource population were not strongly selected, and their genetic variation was large. The pedigree information ( Costa et al, 2015 ) and chip data ( Won et al, 2018 ; Wurtz et al, 2018 ) were widely applied for quantitative trait locus (QTL) mapping. So far, no report on more than 10 million SNP markers used for estimating the heritability of quantitative traits in livestock and poultry is available.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PL and IMF of this resource population were not strongly selected, and their genetic variation was large. The pedigree information ( Costa et al, 2015 ) and chip data ( Won et al, 2018 ; Wurtz et al, 2018 ) were widely applied for quantitative trait locus (QTL) mapping. So far, no report on more than 10 million SNP markers used for estimating the heritability of quantitative traits in livestock and poultry is available.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques can convert farms to research facilities that provide real-time outcomes. An example includes measuring pig aggression [139,140] in the presence of environmental enrichment, (3) Consumer acceptance and enhancement of consumer image of the swine industry: The public expects producers to provide individual attention with good human-animal interaction. While we presume that large commercial producers will become early adopters of technology, precision livestock farming can be farm-size neutral.…”
Section: Limitations and Opportunitiesmentioning
confidence: 99%
“…Owing to these difficulties, only a few studies using omics technologies have been published to date on tail biting behaviour. Genetic association studies have identified a QTL for the number of lesions in Yorkshire pigs after mixing on chromosome 11 [ 142 ]. Being a victim of tail biting was associated with genomic regions on chromosomes 1, 9, 18 and an unassigned region [ 143 ].…”
Section: Omics To Study Tail Bitingmentioning
confidence: 99%